The challenge of identity, education and citizenship for muslims in a pluralistic society : a case study of Malaysia - Hashim, Rosnani (Palgrave Macmillan, 2010)
This chapter examines the path the Malay-Muslims in Malaysia have travelled in establishing and maintaining their identity in the modern context. It examines the educational responses of Malctysia, ,vith a predominantly Mmlim population, in molding Muslim identity within the context and needs of a pluralistic society. The discussion proceeds within two contexts: the first is the most immediate context of colonization that bequeathed !vlalaysia an educational system that catered to the needs of a small elire group, and the second is the lJrger context of Muslim reform movements beginning in the nineteenth century that made education of Muslims an issue. fvlalaysia is one of the very fe,v countries in the Muslim world and in Asia that has, s.inee gaining independence, tried to overhaul its educational system to make it more responsive to the needs ofall its members. While maintaining its Muslim identity.